2022
DOI: 10.3389/fpsyg.2022.904761
|View full text |Cite
|
Sign up to set email alerts
|

Educational Robotics Intervention to Foster Computational Thinking in Preschoolers: Effects of Children’s Task Engagement

Abstract: Computational thinking (CT) is a broadly used term in education to refer to the cognitive processes underlying the application of computer science concepts and strategies of problem-solving. Recent literature has pointed out the value of children acquiring computational thinking skills (i.e., understanding and applying concepts, such as conditionals, iteration, or generalization), especially while learning STEM subjects. Robotics has been used as a tool to introduce computational thinking and STEM knowledge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…From this perspective, the integration of computer science into schools has two main objectives: to offer all students the possibility of accessing computer science and to improve the learning of subjects known as STEAM (Science, Technology, Engineering, Arts and Mathematics) [12] by making the contents more authentic and relevant [13] and helping students with learning to break down a task into simpler ones, formulating and testing hypotheses, exploring and investigating, relating knowledge and coming up with original ideas or solutions. Thus, at a global level, different educational administrations have echoed this need in an increasingly digital world and are integrating computational thinking in their classrooms [14][15][16] as another competence that students must acquire from early childhood and primary education [17][18][19][20][21][22][23] through to secondary education [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, the integration of computer science into schools has two main objectives: to offer all students the possibility of accessing computer science and to improve the learning of subjects known as STEAM (Science, Technology, Engineering, Arts and Mathematics) [12] by making the contents more authentic and relevant [13] and helping students with learning to break down a task into simpler ones, formulating and testing hypotheses, exploring and investigating, relating knowledge and coming up with original ideas or solutions. Thus, at a global level, different educational administrations have echoed this need in an increasingly digital world and are integrating computational thinking in their classrooms [14][15][16] as another competence that students must acquire from early childhood and primary education [17][18][19][20][21][22][23] through to secondary education [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified the use of various technologies, such as coding robots and coding apps, to facilitate the development of CT in young children (Angeli & Valanides, 2020;Bakala et al, 2021Bakala et al, , 2023Papadakis, 2021;Yang, Luo, & Su, 2022). Gerosa et al (2022) and Yang, Ng, and Gao (2022) confirmed the success of coding robots like RoboTito and Matatalab in kindergarten CT learning, while Bers et al (2019) established that children as young as three can begin coding with the KIBO robotics kit.…”
Section: The Role Of Coding Robots and Apps In Enhancing Young Childr...mentioning
confidence: 95%
“…Pada tahun 2006, Jeannette Wing menerbitkan artikel berpengaruh, "Computational Thinking", yang menekankan pentingnya mengajarkan berpikir komputasional kepada siswa (Wing, 2006). Baru-baru ini, diakui bahwa berpikir komputasional dikaitkan dengan keterampilan pemecahan masalah di banyak domain lain (Gerosa et al, 2022;Tang et al, 2020). Misalnya, Computer Science Teachers Association (CSTA) dan International Society for Technology in Education (ISTE) secara umum mendefinisikan berpikir komputasional sebagai kemampuan untuk memecahkan masalah dengan cara yang paling efisien dan efektif melalui pengorganisasian dan analisis data secara logis.…”
Section: Pentingnya Berpikir Komputasional Dalam Pembelajaran Matematikaunclassified